A parametric measure of lactation persistency in dairy cattle - Kamidi, R.E. (Elsevier, 2005)
Current measures of lactation persistency are not uniformly applicable to the variety of lactation curves for individual cows. Moreover, they are either difficult to interpret or are functions of lactation yield and therefore inappropriate. In this study, a simple, robust parametric measure is derived from a perfect fit of cumulative milk yield data to quadratic curves. The curvilinear model is appropriate for trend analysis, a major manifestation of which is persistency. Data fitted to the model were obtained from a total of 194 lactations of 169 cows in 5 mixed-breed herds under conditions varying from a small holding herd in the tropics to research herds in Italy. A negative association between persistency and total lactation yield was observed. The proposed lactation persistency model could result in more accurate estimates and better insight into this trait.